Exporting and environmental performance: Where you export matters - Juan S. Blyde; Mayra A. Ramírez (Inter-American Development Bank (IDB), 2022)
Empirical analyses that rely on micro-level panel data have found that exporters are generally less pollutant than non-exporters. While alternative explanations have been proposed, firm level data has not been used to examine the role of destination markets behind the relationship between exports and pollution. In this paper we argue that because consumers in high-income countries have higher valuations for clean environments than consumers in developing countries, exporters targeting high-income countries are more likely to improve their environmental outcomes than exporters targeting destinations where valuations for the environment are not high. Using a panel of firm-level data from Chile we find support to this hypothesis. A 10 percentage point increase in the share of exports to high-income countries is associated with a reduction in CO2 pollution intensity of about 16%. The results have important implications for firms in developing countries aiming to target high-income markets.
Keywords: F14; F18; Q56; 330; exports; environment; climate change; emissions